The factors of loyalty of social service personnel - Бойко, В. О. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2020)
The article reveals the relevance of the problem under study; relying on the previously developed research base, as well as analyzing the results of various companies in the field of personnel policy. The paper focuses on the fact that for the sustainable development and functioning of the organization, it is not enough to have a high level of training and skills, since the loyalty of staff is not always correlated with the intellectual abilities or skill level of the organization’s employees. Loyal staff is highly reliable, responsible and dedicated to their organization. This, in turn, reduces the likelihood of personnel risks (malfeasance, petty theft, property damage, intentional accidents, etc.). The basic definition of staff loyalty is considered, as well as the essence of the main two approaches: foreign and domestic, which in turn are divided into separate approaches. In the process of reviewing domestic approaches, we paid attention to the following authors: K. Harsky, T. N. Chistyakova, and N. V. Mosienko. among foreign approaches, we focused on such authors as: Howard Becker and Lyman porter. Based on the analysis of these approaches, the author’s definition of staff loyalty is given. We analyze groups of factors that contribute to the formation and increase of staff loyalty: organizational and personal. The article focuses on the study of factors of loyalty of social service personnel. In order to study and structure the factors of loyalty of social service personnel, the author conducted a sociological study, the object of which was employees of the Kharkiv city center of social services for children, families and youth "Trust". 10 employees of this organization were interviewed using a semi-structured interview method. The age of the respondents is from 26 to 58 years, among them: 2 men and 8 women. All respondents have higher education or several higher education institutions.